2005
DOI: 10.1002/mar.20080
|View full text |Cite
|
Sign up to set email alerts
|

On-line product presentation: Effects on mood, perceived risk, and purchase intention

Abstract: Because the Internet purchase of apparel is risky, there is a strong need to develop better visual product presentation on-line that may give some sense of fit and other tactile experience to reduce perceived risk and create pleasurable shopping experiences. Toward this end, the effect of product presentation on consumer responses was examined here. In addition, the relationships among variables were investigated to provide details of the nature of the effect of product presentation. This study employed a 2 ؋ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
269
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(312 citation statements)
references
References 59 publications
(78 reference statements)
10
269
5
1
Order By: Relevance
“…Numerous studies have confirmed that perceived risk affects consumers' attitudes (Featherman & Pavlou, 2003;Lee, Kim, & Fiore, 2010;Park & Kim, 2007;Verhagen, Meents, & Tan, 2006) and purchase intentions (Choi & Lee, 2003;Gaal & Burns, 2001;Han & Chung, 2014;Jin & Koh, 1999;Park, Lennon, & Stoel, 2005). For instance, two online shopping studies found that perceived risk negatively influenced attitudes toward online retailers (Lee et al 2010;Verhagen et al, 2006).…”
Section: Perceived Risk Attitudes and Purchase Intentionsmentioning
confidence: 97%
“…Numerous studies have confirmed that perceived risk affects consumers' attitudes (Featherman & Pavlou, 2003;Lee, Kim, & Fiore, 2010;Park & Kim, 2007;Verhagen, Meents, & Tan, 2006) and purchase intentions (Choi & Lee, 2003;Gaal & Burns, 2001;Han & Chung, 2014;Jin & Koh, 1999;Park, Lennon, & Stoel, 2005). For instance, two online shopping studies found that perceived risk negatively influenced attitudes toward online retailers (Lee et al 2010;Verhagen et al, 2006).…”
Section: Perceived Risk Attitudes and Purchase Intentionsmentioning
confidence: 97%
“…In this case, customer satisfaction is less likely to translate into higher sales at a given level of advertising and promotion costs. On the contrary, in highly concentrated markets it is easier for the customers to overlook the offers of the different competitors (Park, Lennon, and Stoel 2005).…”
Section: Homburg / Luo Neglected Outcomes Of Customer Satisfactionmentioning
confidence: 99%
“…Consumers experience perceived risks, defined as the nature and amount of uncertainty about potential outcomes observed in making a specific decision in the purchasing process (Forsythe & Shi, 2003;Park, Lennon, & Stoel, 2005). Perceived risks experienced during the purchasing process can be categorized as financial (i.e., potential of losing money), performance (i.e., potential for a lack of functionality), physical (i.e., possibility a product may cause harm), psychological (i.e., consistency with self-concept), and social (i.e., negative feedback from others) (Wu & Ke, 2015).…”
Section: Perceived Risks In Online Shoppingmentioning
confidence: 99%